Adolescent Health: A Framework for Developing an Innovative Personalized Well-Being Index - Mastorci, Francesca; Bastiani, Luca; Doveri, Cristina; Trivellini, Gabriele; Casu, Anselmo; Vassalle, Cristina; Pingitore, Alessandro (Frontiers in Pediatrics, 2020)
Adolescence is typically considered a time of good health, but also characterized by an emergence of risk factors that may have long-term consequences for well-being that represents a strong predictors of adverse health outcomes. To assess adolescence well-being through the development of an integrated Well-Being index (WBI) including variables of lifestyle habits, social context, emotional status, and mental skills. 1248 healthy adolescents (Female 48; Male 52%; Mean age 13 SD) were recruited from 5 Italian junior high school, by using KIDSCREEN-52 and cognitive processing using the Stroop Test. School performance was estimated through questions concerning the scholastic achievement. Social context was the most important predictor of perceived well-being (β =.972, SE=.014, p<.000), with parent relation (p<.0001) as the most observed variable. Subsequently WBI was strongly represented by lifestyle habits (β =.954, SE=.017, p<.000) with autonomy (p<0.0001), and emotional status (β =.949, SE=.017, p<.000) with psychological well-being perception (p<0.0001). Finally, mental skills (β=-.1417, SE=.031, p<.0.00) was the least important predictor for the WBI index with science (p<0.0001). Personalised (P) WBI was obtained by the sum of each centred and scaled WBI variable weighted by the corresponding ratio between factor loading and residual variance. Social context was the more important predictor of WBI, followed by lifestyle, emotional factors and lastly mental skills. PWBI allows an integrated and personalised perspective of adolescent’ well-being opening to a cooperation between all members of the school and family community to promote and protect adolescent health. .